Histomorphological study of chorionic villi in products of conception following first trimester abortions - Dr. Shilpa; Dr. Supreetha; Dr. Varshashree (Tropical Journal of Pathology and Microbiology, 2018)
Background: The common problem which occurs in first trimester of pregnancy is miscarriage. Retained products of conception are commonly received specimen for histopathological examination. Apart from confirmation of pregnancy, a careful examination can provide some additional information about the cause or the conditions associated with abortion. Aim: 1. To study various histopathological changes occurring in chorionic villi in first trimester spontaneous abortions and to know the pathogenesis of abortions. Materials and methods: This was a cross sectional retrospective study carried out for over a period of 3 years from January 2015 to January 2018. A total of 235biopsies were obtained from patient with the diagnosis of the first trimester spontaneous abortions were included in this study. Results: In our study most common age group of the abortion was between 21-30 years (63%). Incomplete abortion was the commonest type of abortion (47.7%). Many dysmorphic features were observed in this study like hydropic change (67%), stromal fibrosis (62%), villi with reduced blood vessels (52.7%) and perivillous fibrin deposition. Other features seen were haemorrhage, fibrinoid degeneration, Aria Stella reaction and calcification. Reduced blood vessels in the villi had statistically significant association with stromal fibrosis and hydropic change which was <0.05. Conclusion: Cases with dysmorphic features as seen in the present study may be associated with certain chromosomal abnormalities. Such cases can not only be filtered for cytogenetic work up, but these features can also aid in counselling and planning of future pregnancies. Thus histopathological examination of abortus material is highly recommended.